Routine Histopathological Examination of the Specimen After Laparoscopic Cholecystectomy: Can We Be Brave Enough to Give Up? - Kozan, Ramazan; Özaydın, Safa; Bayhan, Hüseyin; Leventoğlu, Sezai; Karamercan, Ahmet; Anadol, Ahmet Ziya; Şare, Mustafa; Aytaç, Abdülkadir Bülent (Turkish Journal of Gastroenterology, 2021)
investigatethe effect of histopathology results on treatment modality and surgery strategy. The validity of the selective histopathologyapproach was questioned.Methods: The data of patients undergoing laparoscopic cholecystectomy between January 2009 and December 2019 were retrospectivelyanalyzed. The demographics and histopathology results, whether the operation was emergent or elective, and the reasons forconversion to open surgery were recorded. Malignant and precursor histopathology diagnoses were examined, and their relationshipwith the surgical strategy was questioned.Results: A total of 2723 patients were included in the study. Of these patients, 2600 (95.5%) were operated under elective, while 123(4.5%) were operated under emergency conditions. While the surgery was completed laparoscopically in 2685 (98.6%) patients, it wasconverted to open surgery in 38 (1.4%) patients. Age, gender, the presence of primary gallbladder cancer, acute cholecystitis, and xanthogranulomatouscholecystitis in histopathological examination were found to be independent predictive factors for conversion toopen surgery (P < .05). The rate of primary invasive carcinoma in the series was 0.1%.Conclusion: Routine histopathological examination of the gallbladder is important for demonstrating a wide spectrum of pathologicalchanges in this organ. Invasive cancer or precursor lesions can be detected even in patients without any macroscopic abnormality.Histopathological examination also plays a role in determining follow-up, further examination, and treatment modality in addition tothe diagnosis in these patients.